Diagnostics of strength abilities of paralympic athletes - Povrazník, K. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Complex condition diagnosis of athletes is very important for maintaining the health of athletes primarily and secondarily for maintaining and increasing their sports performance. In our contribution, we want to demonstrate the methodology of a complete fitness diagnosis of the strength abilities of the paralympic athletes in alpine skiing. The results are important for planning their individual fitness training in eliminating strength imbalances.